The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/aoc.4774
|View full text |Cite
|
Sign up to set email alerts
|

Cu nanoparticles immobilized on modified magnetic zeolite for the synthesis of 1,2,3‐triazoles under ultrasonic conditions

Abstract: Magnetically recoverable copper nanoparticle‐loaded natural zeolite (CuNPs/MZN) as an efficient catalyst was synthesized. The Fe3O4 magnetic nanoparticles were immobilized into the pores of natural clinoptilolite zeolite, which were modified with epichlorohydrine and ethylenediamine species and then CuNPs were decorated on the surface of functionalized zeolite (CuNPs/MZN). The catalysts were successfully characterized by Fourier transform‐infrared, CHN, thermogravimetric analysis, inductively coupled plasma, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…[187][188][189][190][191][192] Supported NPs offer several advantages over the use of unsupported NPs, such as better control of metal dispersion and particle morphology, inhibition of particle aggregation, and generally better reuse of the catalytic system. Given these attributes, different supported and recyclable CuNPs were employed in CuAAC reactions, among the supports employed are alumina, 193 aluminum oxyhydroxide, 194 montmorillonite, 195 MOF, [196][197][198] Cellulose, 199 SBA-15, 200 Zeolite, 201 and more recently graphene oxide. 202 In a study published in 2019 by Gholinejad et al 203 clinochlore was first reported as a very inexpensive and available support for the stabilization of copper nanoparticles and their application as a recyclable catalyst for the formation of 1H-1,2,3-triazoles at room temperature and in aqueous medium.…”
Section: Scheme 25mentioning
confidence: 99%
“…[187][188][189][190][191][192] Supported NPs offer several advantages over the use of unsupported NPs, such as better control of metal dispersion and particle morphology, inhibition of particle aggregation, and generally better reuse of the catalytic system. Given these attributes, different supported and recyclable CuNPs were employed in CuAAC reactions, among the supports employed are alumina, 193 aluminum oxyhydroxide, 194 montmorillonite, 195 MOF, [196][197][198] Cellulose, 199 SBA-15, 200 Zeolite, 201 and more recently graphene oxide. 202 In a study published in 2019 by Gholinejad et al 203 clinochlore was first reported as a very inexpensive and available support for the stabilization of copper nanoparticles and their application as a recyclable catalyst for the formation of 1H-1,2,3-triazoles at room temperature and in aqueous medium.…”
Section: Scheme 25mentioning
confidence: 99%
“…According to previous reports, various metal‐based catalysts, including Ag, Fe, Li, Ni, Pd, In and Au, have been reported for the synthesis of propargylamines . In this view, copper and zinc catalysts are the most important for the synthesis of propargylamine derivatives, and good results have been achieved in the presence of these catalysts …”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] Among them, magnetic iron oxide nanoparticles have received a remarkable attention for use in catalytic reactions, because of their high catalytic activity and easy separation. [ 22 ] Recently, various heterogeneous copper catalytic systems for the synthesis of 1,4‐disubstituted 1,2,3‐triazoles from unstable aryl azides and terminal alkynes have been reported, [ 19,23 ] whereas there have been few reports on one‐pot multicomponent synthesis of 1,2,3‐triazoles from sodium azide, alkynes, and aryl halides as the azide precursors, which most of them have used homogeneous copper catalysts. [ 24 ] Therefore, it might be desirable to develop new methods for the regioselective synthesis of triazoles using effective and recyclable catalytic systems.…”
Section: Introductionmentioning
confidence: 99%